2019
DOI: 10.1016/j.freeradbiomed.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation by NRF2 in aging and disease

Abstract: NRF2, a transcription factor that has been deemed the master regulator of cellular redox homeostasis, declines with age. NRF2 transcriptionally upregulates genes that combat oxidative stress; therefore, loss of NRF2 allows oxidative stress to go unmitigated and drive the aging phenotype. Oxidative stress is a common theme among the key features associated with the aging process, collectively referred to as the "Hallmarks of Aging", as it disrupts proteostasis, alters genomic stability, and leads to cell death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
229
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(261 citation statements)
references
References 50 publications
8
229
1
2
Order By: Relevance
“…In the present study, we also evaluated Nrf2, a master regulator of cellular redox homeostasis (Schmidlin et al, 2019), and HO-1, one of the key enzymes that suppresses oxidative stress and may contribute to cardioprotection (Cao et al, 2015). We observed that Nrf2 was moderately/strongly expressed in the cytoplasm of lean cardiomyocytes (Figure 3A), but shows significantly decreased expression in ob/ob heart, reaching only very weak/weak expression ( Figure 3B).…”
Section: Heart Oxidative Stress Evaluationmentioning
confidence: 82%
“…In the present study, we also evaluated Nrf2, a master regulator of cellular redox homeostasis (Schmidlin et al, 2019), and HO-1, one of the key enzymes that suppresses oxidative stress and may contribute to cardioprotection (Cao et al, 2015). We observed that Nrf2 was moderately/strongly expressed in the cytoplasm of lean cardiomyocytes (Figure 3A), but shows significantly decreased expression in ob/ob heart, reaching only very weak/weak expression ( Figure 3B).…”
Section: Heart Oxidative Stress Evaluationmentioning
confidence: 82%
“…In fact, abnormal protein S-glutathionylation is related to diverse cellular detrimental changes, including protein aggregation, protein degradation, apoptosis and mitochondrial dysfunction [215]. A thiol redox system consisting of the glutathione system (glutathione/glutathione reductase/glutaredoxin/glutathione peroxidase) and the thioredoxin system (thioredoxin/thioredoxin peroxidase (peroxiredoxins)/sulfiredoxin/thioredoxin reductase [216] are believed to be the major players in redox status regulation [99,[217][218][219]. Further, the thioredoxin system is an important thiol/disulphide redox controller ensuring the redox homeostasis [220].…”
Section: Nad(p)h Quinone Oxidoreductase-1 Nqo1mentioning
confidence: 99%
“…This value is of the same magnitude to those found for genes that are very well known VDR targets: genes related to calcium homeostasis such as parvalbumin, the calcium exchanger NCX1 (SLC8A2-2) or related to antioxidant defence genes such as glutathione peroxidase, or NRF2 (NFE2L2-4) to cite a few [24,28]. It is interesting remembering that NRF2, in turn, activates the transcription of antioxidant and detoxifying genes such as catalase, superoxide dismutases or thioredoxin reductase [72]. In this context, the beneficial effects of calcitriol, as a natural NRF2 inducer, are in agreement with one of the emerging therapies for FA is based on the activation of NRF2 including sulphoraphane [73], dimethyl fumarate [74] or omaveloxolone [75,76].…”
Section: The Beneficial Role Of Calcitriol In Neurodegenerative Diseamentioning
confidence: 71%